GENDER's storytelling training program: evaluating the Sep 2024 - Dec 2025 course - Econnect Communication (CGIAR GENDER Impact Platform, 2024)
- In 2024, a total of 15 science communicators completed an 8-module online training course to prepare, produce, pitch and publish stories on gender-responsive agricultural solutions. The course was held between 10 September and 26 November and was rated as highly valuable (92%) by most participants with the rest rating it as valuable. - Feedback from trainees has been overwhelmingly positive, with a special emphasis on the value of having a personal mentor supporting each trainee from story idea to publication. Trainees’ self-reported skills assessment indicates significant growth in skills, particularly a notable increase in skills regarding researching a story, structuring and writing a story, and understanding and including gender aspects in a story. - As of 24 January 2025, four participants have published stories in media outlets, six have pitched their stories, three are ready to pitch their stories and another two are finalizing their stories ready to pitch. - The third GENDER storytelling training program generated new or revised outputs for the CGSpace including: 3 new training materials (Gender-responsive solutions in agriculture, Finding story ideas, Potential outlets for gender-responsive agriculture stories) and an updated 40+ page training guide. - The GENDER storytelling training program resources published on CGSpace appear to be very popular with 852 downloads of materials from the CGSpace since materials were loaded in late 2023. - With 150 people applying to participate in this workshop series, demand is very high for the training program. We recommend continuing the training in 2025 but starting the training earlier in the year (between February and July) to avoid end of year work pressures and conflicts. We also recommend incorporating face-to-face sessions (like for the second training program held in 2023), where possible.